Determination of maleic hydrazide residues in onion - Bursić Vojislava (Ratarstvo i Povrtarstvo, 2010)
A simple HPLC determination method of maleic hydrazide residues in onions was introduced. The homogenized onion samples were extracted with methanol. The crude ex- tract was purified on SPE SampliQ SCX column. The maleic hydrazide was analyzed by HPLC with UV detection of 313 nm. The HPLC separation was performed on SynChropak Q column with 0.25 M phosphate buffer as the mobile phase. The recoveries of maleic hydrazide from the spiked onions with 1.5, 2.0, 3.0, 5.0, 7.0 and 10.0 mg ml-1, ranged from 89-103%. The detection limit of maleic hydrazide was 0.4 mg ml-1, and the quantification limit was 1.25 mg ml-1. The linearity coefficient was 0.9998. Such an optimized method was applied to the determination of residue content of maleic hydrazide in onions, treated with Royal MH-30 in the amount of 8.0 and 12.0 l ha-1. The samples were analysed after 8, 16 and 25 days from the moment of spraying. The obtained values of maleic hydrazide residues were below the maximum tolerable amount in the Republic of Serbia (10 mg kg-1), as well as the amount regulated by the EU (15 mg kg-1). .